PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP PRESTASI KERJA KARYAWAN PT. PLN (PERSERO) AREA JEMBER - Fatimah, Irma (Universitas Pendidikan Ganesha, 2018)
This study aimed to test the influence of the implementation of responsibility accounting of the job performance. This research is used 60 samples of respondents. Data obtained by the method of purposive sampling. The data was collected using a interviews and quistionnaire. Research hypotesis were tasted using simple regression method. Based on hypothesis testing the result showed of this research, it can be concluded that the implementation of responsibility accounting effect significantly to the job performance. Where the result of analysis on the responsibility accounting have a significant effect on job performance show t count (19,783) > t table (1,67203).